PELAKSANAAN PROGRAM BOARDING SCHOOL DALAM PEMBENTUKAN AKHLAK SISWA DI SMAS MTA SURAKARTA - Fatimah Dian Wulandari; Triono Ali Mustofa (Jurnal Bilqolam Pendidikan Islam, 2024)
The formation of morals cannot be separated from the world of eduacation is one of the foundations for forming an increasingly well-developed civilization. The formation of morals is not just theory, but rather practice and habituation in everyday life. So that with habit, every student will become accustomed to it. As in the implementation of the boarding school program carried out at SMAS MTA Surakarta. The diverse backgrounds of students accepted create challenges for an educational institution. Caregivers must be able to condition and implement appropriate strategies for implementing this program so that it can run according to the desired goals. This research uses field research methods, with data collection techniques including documentation, interviews and observation. Meanwhile, the data analysis technique used by researchers is to analyze the findings, which are expressed in written form and arranged systematically and structured. The result of this research are as follow: 1)that the implementation of the Boarding School program at SMAS MTA Surakarta is going well. 2)There are no significant obstacles, meaning that every student is able to participate in the on going learning. 3) Forming students morals through the Boarading School program at SMAS MTA Surakarta has proven to be effective. This can be seen from the guidance that religious activities at SMAS MTA Surakarta have an influence on their personal lives